Clinical and Neuropathological Aspects of Chronic Herpetic Encephalitis: An In-Depth Review - Hakimova Sokhiba Ziyadullovna; Gaffarova Parvina Abdurafikovna; Zayniyev Muzaffarjon Xurshedjon ugli (American Journal of Biomedicine and Pharmacy, 2025)
Chronic herpetic encephalitis (CHE) is a rare, slowly progressing inflammatory disease of the central nervous system (CNS), caused by the persistent presence of herpes simplex virus type 1 (HSV-1) in neural tissue. Unlike acute herpetic encephalitis, the chronic form manifests with long-term neurological impairment, mimicking degenerative and autoimmune diseases. This paper aims to explore the pathogenesis, clinical features, diagnostic approaches, imaging findings, therapeutic strategies, and prognosis of CHE. Given its insidious onset and diagnostic difficulty, awareness of this condition is critical among neurologists and infectious disease specialists to avoid underrecognition and mistreatment.